Pengembangan UMKM Melalui Geoproduk untuk Geopark Gorontalo - Butolo, Ivana (Research and Development Agency Ministry of Home Affairs, 2022)
Geopark is an area that combines the uniqueness of geology, biodiversity, and cultural diversity that is managed for the needs of conservation, education, and sustainable economic development of the community. The existence of this Geopark has opened up opportunities and become a great chance for local communities. Gorontalo province has the biggest potential natural resources for development; in this matter, we need local creativity to build efforts in special characters and also unique for itself. The Gorontalo Geopark is currently undergoing improvements for the development of MSMEs to create innovative products related to the Geopark and actively contribute to the local economic growth of the community. This study aims to understand the existence of geo products as part of MSMEs and find out how the strategy of geo product development for local economic growth can support the development of the Gorontalo geopark. This study uses a qualitative descriptive method with primary data collection techniques through observation, interviews, and secondary data obtained from the relevant agencies. The results showed that geo products are one of the first steps in developing MSMEs to improve the community's economy, although, in practice, there are still problems. In this condition, the local government must formulate a policy strategy for developing MSMEs through geo product, namely fixing the database, increasing community capacity, creating innovation, creating geopark branding, optimizing the use of technology, stakeholder collaboration also promotion strategy. This policy strategy is formulated so that the presence of geo products can support the Gorontalo geopark in improving community welfare.